57.1k views
4 votes
Which equation demonstrates the additive identity property?

(7+4) +(7-41) = 14
© (7+4)+ 0 = 7+41
O (7+4)(1) = 7+41
o (7+41)+(-7-41) = 0

User LeWoody
by
5.7k points

2 Answers

4 votes

Answer:

(7 + 4 i) + 0 = 7 + 4 i

Explanation:

User Linus Borg
by
5.2k points
4 votes

Answer:

Explanation:

Solve for o in the equation (7 + 4) + (7 - 41) = 14©(7 + 4) + 0 = 7 + 41o(7 + 4)(1) = 7 + 41o(7 + 41) + ( - 7 - 41) = 0

We first need to simplify the expression removing parentheses

Simplify 41o(7 + 4): Distribute the 41o to each term in (7+4)

41o * 7 = (41 * 7)o = 287o 41o * 4 = (41 * 4)o = 164o

Our Total expanded term is 287o + 164o

Simplify 41o(7 + 41): Distribute the 41o to each term in (7+41)

41o * 7 = (41 * 7)o = 287o 41o * 41 = (41 * 41)o = 1681o

Our Total expanded term is 287o + 1681o

Our updated term to work with is (7 + 4) + (7 - 41) = 14©(7 + 4) + 0 = 7 + 287o + 164o(1) = 7 + 287o + 1681o + ( - 7 - 41) = 0

We first need to simplify the expression removing parentheses

Simplify 164o(1): Distribute the 164o to each term in (1)

164o * 1 = (164 * 1)o = 164o Our Total expanded term is 164o

Our updated term to work with is (7 + 4) + (7 - 41) = 14©(7 + 4) + 0 = 7 + 287o + 164o = 7 + 287o + 1681o + ( - 7 - 41) = 0

Step 1: Group variables: We need to group our variables (7 and 14©(7. To do that, we subtract 14©(7 from both sides (7 - 14©(7 = 14©(7 - 14©(7

Step 2: Cancel 14©(7 on the right side: 0o = 0 Step 3: Divide each side of the equation by 0

0o 0 = 0 0 o =

User Lorne Laliberte
by
5.6k points